INVENTARISASI JENIS-JENIS HAMA PADA PERTANAMAN CABAI (Capsicum annum L.) DI KELURAHAN KAKASKASEN I KOTA TOMOHON - Rafel S. Saroinsong; Daisy S. Kandowangko; Christina L. Salaki; Caroulus S. Rante (COCOS, 2014)
ABSTRACTRAFEL S. SAROINSONG. 100318024. 2014. Inventory Types of Pests on Cropping Chilli (Capsicum annum L.) in the Village Kakaskasen I, Tomohon (Under the guidance of Daisy S. Kandowangko as chairman, Christina L. Salaki and Caroulus S. Rante as a member).This study aims to inventory the types of crop pests and its dominance in chilli (Capsicum annum L.) Organic and Conventional. Field research has been conducted on chilli crop in Village Kakaskasen, Tomohon. Laboratory observations carried out at the Laboratory of Entomology and Pest Plants, Faculty of Agriculture, University of Sam Ratulangi. Research carried out for approximately six months which began in March to August 2014. Observations were made in pepper organic and conventional generative phase. Sampling was done by using an insect net with five swing, Yellow Sticky Trap and attractant (petrogenol). Sampling was conducted over 10 times since crop enters the generative phaseResults showed six orders of insect pests associated to the chilli crop Organic and Conventional namely: Order of Coleoptera (Family Scarabaeidae and Curculionidae); Order of Hemiptera (Family Coreidae and Pentatomidae); Order of Homoptera (Family Aphididae); Order of Thysanoptera (Family Thripidae); Order Diptera (Family Tephritidae); and Order of Lepidoptera (Family Noctuidae). Insects dominate Organic chilli planting area is the Order Diptera (Family Tephritidae), whereas the Conventional chilli planting area is dominated by the Order Coleoptera (Family Scarabaeidae).Keywords : Capsicum annum L., Chili, Kakaskasen I, Tomohon